Energy and Sustainability IV 2013
DOI: 10.2495/esus130261
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the reaction at the solution interface of pyrite during oil agglomeration for developing desulfurization and coal cleaning efficiency

Abstract: Recently, large amounts of waste fine coals have been produced which are difficult to treat because of the high ash content and inorganic sulfuric compounds. In order to make efficient use of waste fine coal, the retrieval technique is necessary for recovery of coal combustible content from fine waste coals. Nowadays a floatation process is able to operate, but it is impractical for developing countries due to high costs. An oil agglomeration process can deal with these problems. In this study, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is worth to develop different technologies for controlling air pollutants emitted from fuel utilization. Some achievements in this study have been applied and linked with other studies reported during the 4th International Conference on Energy and Sustainability [17][18][19].…”
Section: Co 2 Gasifi Cation Reactivity Of Waste Wood Char Samplesmentioning
confidence: 71%
“…It is worth to develop different technologies for controlling air pollutants emitted from fuel utilization. Some achievements in this study have been applied and linked with other studies reported during the 4th International Conference on Energy and Sustainability [17][18][19].…”
Section: Co 2 Gasifi Cation Reactivity Of Waste Wood Char Samplesmentioning
confidence: 71%
“…In addition, the combustion characteristics of aggregates were determined by thermogravimetric-derivative thermogravimetric (TG-DTG) analyses. In this study, more detailed experiments were carried out and added different results with a conference paper published in the 4th International Conference on Energy and Sustainability [9].…”
Section: Introductionmentioning
confidence: 99%